2017
DOI: 10.1001/jamacardio.2017.4069
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity With Risk of Major Cardiovascular Diseases in Chinese Men and Women

Abstract: Among Chinese adults, higher occupational or nonoccupational physical activity was associated with significantly lower risks of major CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
104
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 46 publications
(64 reference statements)
15
104
2
1
Order By: Relevance
“…The ndings highlight the pivotal role of childhood SES, childhood health status, and health care resources in risk of heart disease among Chinese populations. Some ndings of this study are consistent with prior studies [2,5,10,13,16,26]; age was the most important predictor of morbidity related to heart disease. However, gender, education level, household registration status, overweight, obesity, hypertension, unhealthy behaviors (e.g., smoking), and functional loss in later life were also signi cantly associated with heart disease morbidity in later life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ndings highlight the pivotal role of childhood SES, childhood health status, and health care resources in risk of heart disease among Chinese populations. Some ndings of this study are consistent with prior studies [2,5,10,13,16,26]; age was the most important predictor of morbidity related to heart disease. However, gender, education level, household registration status, overweight, obesity, hypertension, unhealthy behaviors (e.g., smoking), and functional loss in later life were also signi cantly associated with heart disease morbidity in later life.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research identi ed a range of individual-level social and health factors related to heart disease [10][11][12][13][14]. Speci cally, recent Chinese studies identi ed signi cant associations between unhealthy behaviors (e.g., smoking) and heart disease [10,11,13]. Furthermore, overweight and obesity were found to be the main risk factors for hypertension and dyslipidemia, which further increase the risk of heart disease [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increased prevalence of CHD can be observed in general population and not exclusively in patients with diabetes, which was considered as an alteration in disease patterns from infectious diseases to non-infectious diseases in developing countries [23]. It has been suggested that the ageing population, the western lifestyle, the prevalence of obesity, dyslipidemia, and other metabolic disorders contribute to the disease together [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…As for exercise, guidelines recommend at least 2.5 hours of moderate exercise, or 75 minutes of intense exercise every week. In a commentary in JAMA, Salim Yusuf and associates write, "Regular physical activity is one of the simplest ways, for individuals and populations to reduce the risk of premature death and incident cardiovascular disease [45,46].…”
Section: Discussionmentioning
confidence: 99%